ANALISIS KINERJA SAHAM SYARIAH SEKTOR PERTANIAN DENGAN MENGGUNAKAN METODE SHARPE, TREYNOR, DAN JENSEN - Juwenah, Firman Hidayat (Program Studi Akuntansi, Universitas Kuningan, 2017)
This research is aimed to detect Performance of Sharia Stock Agricultur Sector in Indonesia, especially kind of Stock of within research period 2012-2016. The performance measuring method that is used is Sharpe, Treynor, and Jensen Method. The Data which is used in this research is secondary data by using sample interpretation technique, use purposive sampling. Analysis Technique which is used in this research is decriptive with quantitative approach. Ã‚Â The performance of Sharia StockÃ¢â‚¬â„¢s by using SharpenÃ¢â‚¬â„¢s Method, its founded four Sharia Stock which have Under Performance , those are: PT. Astra Agro Lestari Tbk (AALI), PT Gozco Plantations Tbk (GZCO), PT Sampoerna Agro Tbk (SGRO), dan PT Salim Ivomas Pratama Tbk (SIMP), and also there are five Sharia Stock which have out perform, those are: PT BISI International Tbk (BISI), PT Bumi Teknokultura Unggul Tbk (BTEK), PT Dharma Samudera Fishing Industries Tbk (DSFI), PT Inti Agri Resources Tbk (IIKP), dan PT PP London Sumatra Indonesia Tbk (LSIP).The Performance of Sharia StockÃ¢â‚¬â„¢s by using Treynor Method, there are five Sharia Stock which have under perform, those are PT. Astra Agro Lestari Tbk (AALI), PT Gozco Plantations Tbk (GZCO), PT PP London Sumatra Indonesia Tbk (LSIP), PT Sampoerna Agro Tbk (SGRO), dan PT Salim Ivomas Pratama Tbk (SIMP), and also there are four Sharia Stock which have out perform, Those are PT BISI International Tbk (BISI), PT Bumi Teknokultura Unggul Tbk (BTEK), PT Dharma Samudera Fishing Industries Tbk (DSFI), dan PT Inti Agri Resources Tbk (IIKP).For Sharia StockÃ¢â‚¬â„¢s performance by using Jensen Method cant be achieved the decision whether sharia stock has out perform or under perform.